“Modified Bitumen Grade (85-100) for Use in Domestic Bituminous Mixtures” - سلطان بسام (Latakia University Journal -Engineering Sciences Series, 2021)
The use of bitumen varies according to the climatic condition. Bitumen with high penetration is preferred for cold regions, while hot regions require harder bitumen. This research aims to verify the possibility of using bitumen (85-100) after modifying the use of two types of polymers (SBS, PP) with ratios of (3, 4, 5%) by weight of bitumen for use as a binder in the manufacture of local bituminous mixtures and to increase its resistance to high temperatures and increase its reluctance to different climatic conditions, as the bitumen (85-100) loses many of its properties due to the short-term fatigue that it is exposed to during its production at high temperatures. The results showed that the penetration decreases with increasing polymer addition rate, the remaining penetration increases with increasing polymer addition rate, softening point increases when adding the polymer, which indicates an improvement in the bituminous resistance to deformation at higher temperatures. The study concluded that the use of SBS (5%) is an ideal ratio for bitumen modification (85-100) and can be used in the production of local bituminous mixtures.